ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
Remodeling the immune microenvironment and scavenging excess reactive oxygen species (ROS) are considered effective strategies for treating rheumatoid arthritis (RA). Methotrexate (MTX), a first-line drug, can correct the imbalance between helper T-cell type 17 and regulatory T cells (Th17/Treg) and inhibit the proliferation and migration of fibroblast-like synoviocytes (FLSs). However, it lacks antioxidant and macrophage regulatory functions, is prone to systemic toxicity, and has poor solubility. In this study, MTX and oxidized Bletilla striata polysaccharide (OBSP) were conjugated and self-assembled into MTX-ss-OBSP NPs via disulfide bonds to integrate macrophage-polarizing and antioxidant activities. These nanoparticles were loaded into a novel ROS-responsive oxidized hyaluronic acid-3-aminophenylboronic acid-hyaluronic acid (OHA-PBA-HA) hydrogel, yielding MTX-ss-OBSP NPs@OHA-PBA-HA. This injectable hydrogel exhibits ROS-triggered drug release, reduces ROS levels, promotes M2 macrophage polarization, and modulates cytokine secretion (decreasing IL-6/TNF-α; increasing IL-10). In vivo experiments demonstrated that the hydrogel blocks bone erosion, inhibits synovial inflammation, protects cartilage, and regulates M1/M2 and Th17/Treg balances while significantly reducing MTX-induced hepatotoxicity and nephrotoxicity. Compared with free MTX, this nanoparticle-loaded hydrogel accelerates the resolution of RA inflammation with superior safety. Therefore, this responsive hydrogel system represents a promising candidate for clinical RA treatment by integrating immune remodeling and antioxidant therapy.